Strategi Penerapan Produksi Bersih (Clean Production) Di Pabrik Kelapa Sawit PT. SPA - Widodo, Teguh Sugeng Rahayu; Suwondo; Zulkifli (Program Studi Magister Manajemen Lingkungan, 2024)
The palm oil industry is projected to reach 240 million tons of production demand in 2050, which requires efficient processing plants with waste handling according to standards. Palm Oil Factory PT. SPA, focuses on processing palm oil and producing palm oil (CPO) and palm kernel. Solid, liquid and gas waste are by-products of processing. The concept of clean production is proposed as a holistic solution with positive ecological, economic, social and technical impacts. waste and losses at various production stations, emphasizing the need to reduce quantity and improve quality. Scattered palm fruit waste and oil leaks create a high risk and uncomfortable environment for workers. This research aims to analyze the clean production strategy at the PT Factory. Palm Oil SPA, evaluating implementation, identifying dominant factors, and setting strategic priorities. Field surveys, observations and interviews were used with the Analytical Hierarchy Process (AHP) method for quantitative descriptive analysis. The results show an effective housekeeping program as the main strategy, with employee understanding, awareness and participation as the main factors. Improvements need to be implemented, underscoring the importance of clean production in palm oil mills.